(untitled) (Research, Society and Development, 2022)
Objective: To understand from the state of the art how the breastfeeding process occurs in the prison context. Methodology: Integrative literature review, descriptive, exploratory, qualitative, using the PICo and PRISMA-ScR Strategy. They were realized through 2 journals and 3 databases, with the help of boolean operators "OR" and "AND", between the years 2015 to 2020. Results: 22 studies were found, and 6 articles were used for the sample. Resulting in three categories: (I) The difficulties of the experience of nursing women in the prison system; (II) The consequences of breastfeeding in the Prison System for the mother-baby binomial; (III) The perspective of nursing professionals to ensure, promote and support breastfeeding inside prison. Final considerations: Several factors influence breastfeeding unfavorably, such as physical psychosocial aspects, restriction and neglect of the rights of the mother-child binomial. Assistance with the biomedical model implies the quality of care, promotion and maintenance of intracárcere breastfeeding.